2007
DOI: 10.1016/j.str.2007.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of the Pilus Retraction Motor PilT Suggest Large Domain Movements and Subunit Cooperation Drive Motility

Abstract: PilT is a hexameric ATPase required for bacterial type IV pilus retraction and surface motility. Crystal structures of ADP- and ATP-bound Aquifex aeolicus PilT at 2.8 and 3.2 A resolution show N-terminal PAS-like and C-terminal RecA-like ATPase domains followed by a set of short C-terminal helices. The hexamer is formed by extensive polar subunit interactions between the ATPase core of one monomer and the N-terminal domain of the next. An additional structure captures a nonsymmetric PilT hexamer in which appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
208
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(223 citation statements)
references
References 57 publications
(80 reference statements)
13
208
0
Order By: Relevance
“…Recent studies of BfpD have shown that while all six members of a BfpD hexamer bind ATP, only alternating subunits interact with the BfpE peptide (Crowther et al, 2005), a finding that is consistent with current models of the pilus as a three-start helix (Ramboarina et al, 2005;Craig et al, 2004Craig et al, , 2006 (Satyshur et al, 2007), showing that heterogeneity in the conformational state of individual subunits within the hexameric assembly is likely to be a common feature of these proteins.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Recent studies of BfpD have shown that while all six members of a BfpD hexamer bind ATP, only alternating subunits interact with the BfpE peptide (Crowther et al, 2005), a finding that is consistent with current models of the pilus as a three-start helix (Ramboarina et al, 2005;Craig et al, 2004Craig et al, , 2006 (Satyshur et al, 2007), showing that heterogeneity in the conformational state of individual subunits within the hexameric assembly is likely to be a common feature of these proteins.…”
Section: Discussionsupporting
confidence: 78%
“…While the functions of the WA and WB motifs are well characterized, those of the Asp and His Box motifs remain largely unexplored, despite their broad conservation in the secretion NTPase family. Based on limited structural and mutagenesis data, residues of the Asp and His Boxes are likely to contribute to nucleotide binding and/or sensing as well as subunitsubunit interactions (Satyshur et al, 2007;Robien et al, 2003). In this work we demonstrate that the three motor proteins in P. aeruginosa are bona fide ATPases, and we use a site-directed mutagenesis approach to show that for their function all three require specific invariant residues within the characteristic secretion NTPase motifs.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Whatever aspect of Tfp biology is to be studied, pilus retraction must be taken into account because it generates remarkable mechanical forces (25), likely promoted by domain movements within PilT (26). PilT-powered retraction is indispensable for intimate adhesion (27,28), twitching motility (7,8), competence for DNA transformation (29) and signaling to host cells (30), yet it must be counteracted to achieve efficient biogenesis of pilus filaments.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli TOP10 (Invitrogen, Carlsbad, CA) was used for cloning experiments, whereas BL21(DE3) was used for protein expression and purification. A methionine auxotroph of the latter strain was used for selenomethionine labeling as described (26,35). To facilitate crystallization, we engineered a strain producing a PilX protein missing the first 28 residues of the mature protein.…”
Section: Detailed Methods Are Described In Si Materials and Methodsmentioning
confidence: 99%